A stress-reduction eHealth intervention for healthcare workers in primary care settings: an implementation study - Garcia-Vazquez, Blanca; Muñoz-Sanjosé, Ainoa; Fernández-López, Andrea; Pérez-de-Ciriza, Irene; Nocete-Navarro, Luis; Almaraz-Garzón, Elena; Martín-Palacios, María Teresa; Novella, Blanca; Bravo-Ortiz, María Fe; Ayuso-Mateos, José Luis; Bayón, Carmen; Mediavilla, Roberto (Frontiers in Public Health, 2025)
IntroductionHealthcare systems across Europe are facing significant challenges in retaining and recruiting healthcare workers (HCWs). Mental health problems, including anxiety, depression, and burnout, are major drivers of turnover. Although some psychological interventions, particularly eHealth tools, are effective, they are rarely tested under real-world conditions, widening the research-implementation gap. This study evaluates the implementation outcomes of an eHealth intervention that was shown to reduce anxiety and depression among frontline HCWs during the COVID-19 pandemic.MethodsThe study was conducted at a primary care centre affiliated with Hospital Universitario La Paz in Madrid, between October 2023 and February 2024. The intervention “Doing What Matters in Times of Stress” (DWM), consisted of a web-based, self-help tool and was offered in hybrid and remote formats. Mixed methods were employed to assess key implementation outcomes from Proctor’s framework, combining quantitative data from pre- and postintervention assessments with qualitative insights from interviews.ResultsSeventeen participants were included in the study, with 59% choosing the hybrid format and 41% selecting remote sessions. Participation rate was 44% and retention rates were 80 and 100% for the hybrid and remote formats, respectively. The intervention was perceived as acceptable, appropriate, and feasible. Flexible delivery formats and robust group dynamics, particularly in the hybrid format, were identified as key contributors to the intervention’s success, enhancing group cohesion and fostering empathy among participants. Barriers, such as stigma and time constraints were identified, while enabling factors included practical content and flexibility.ConclusionThis study evaluated the fidelity, feasibility, acceptability, and appropriateness of DWM intervention and remote/hybrid delivery formats among HCWs at a primary care centre in Madrid. Data suggests future studies should maintain hybrid and remote delivery formats and address specific access challenges. These findings provide crucial insights for expanding mental health interventions for HCWs across diverse settings, with implications for public health policy.